2011
DOI: 10.1016/j.jnt.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Diophantine equations with products of consecutive values of a quadratic polynomial

Abstract: Available online xxxx Communicated by Michael E. Pohst MSC: primary 11D09 secondary 11B85 Keywords: Diophantine equation Irreducible quadratic polynomials Chebyshev's inequality Let a, b, c, d be given nonnegative integers with a, d 1. Using Chebyshev's inequalities for the function π (x) and some results concerning arithmetic progressions of prime numbers, we study the Diophantine equation n k=1ak 2 + bk + c = dy l , gcd(a, b, c) = 1, l 2,where ax 2 + bx + c is an irreducible quadratic polynomial. We provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In subsequent work by Fang [8], his technique was applied to products A f (m) corresponding to the polynomials 4x 2 + 1 and 2x 2 − 2x + 1. Yang, Togbé and He [12] proved that for any irreducible quadratic polynomial f (x) ∈ Z[x], there exists a prime p with ord p (A f (m)) = 1 if m ≥ C, where C is a computable constant depending on the coefficients of f (x). Furthermore, the above problem has been investigated by many authors for polynomials of the form f (x) = x k + 1, where k is an odd positive integer.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In subsequent work by Fang [8], his technique was applied to products A f (m) corresponding to the polynomials 4x 2 + 1 and 2x 2 − 2x + 1. Yang, Togbé and He [12] proved that for any irreducible quadratic polynomial f (x) ∈ Z[x], there exists a prime p with ord p (A f (m)) = 1 if m ≥ C, where C is a computable constant depending on the coefficients of f (x). Furthermore, the above problem has been investigated by many authors for polynomials of the form f (x) = x k + 1, where k is an odd positive integer.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Clearly, (8,19) is a solution of (3). For each solution ( , ) of (3), the map sends ( , ) to (9 + 4 + 4, 20 + 9 + 10), which gives another solution of (3).…”
Section: Resultsmentioning
confidence: 99%
“…Fang [4] confirmed another similar conjecture posed by Amdeberhan et al [1] to the products of quadratic polynomials ∏︀ =1 (4 2 +1) and ∏︀ =1 (2 2 −2 +1) are not perfect squares. Yang et al [8] studied the Diophantine equation…”
Section: Introductionmentioning
confidence: 99%
“…Shortly, Cilleruelo [3] proved the conjecture for P 1,1 (n), where he showed that P 1,1 (n) is square only for n = 3, and Fang [4] established the conjecture for P 4,1 (n). Yang, Togbé, and He [9] found all positive integer solutions to the equation P a,c (n) = y l for coprime integers a, c ∈ {1, . .…”
Section: Introductionmentioning
confidence: 99%